SOCIAL MEDIA MARKETING IN SPORTS AND USING SOCIAL MEDIA PLATFORMS FOR SPORTS FAN ENGAGEMENT - Hussain, Ghulam; Naz, Tabssum; Shahzad, Naeem; Bajwa, Muhammad Javed (The journal of contemporary issues in business and government, 2021)
Background: Social media is one of the most frequently utilized platforms to share all news and information nowadays. Therefore, it remains an effectual method towards approaching the target people by using social media so it is becoming most popular for supporting fan engagement and marketing through social media. Illustration content like videos is an effectual method for conveying messages and engaging with fans. Therefore the research is aimed at examining and finding the effectiveness of the using social media platforms for fan engagement. Methods: The standard questionnaire was adapted from past researches and a cross-sectional survey method was conducted. The sample size was 384 out of these sample size, there were 225 males and 161 females. Data about this research was collected and then analyzed by using SPSS version 23. Results: The research showed that the majority of the sample population prefers to watch a video. They present the explanations such as it presents an obvious message as well as eliminates all confusions. It remains time saving as well as attracting for the watchers. Majority of the responses agree that social media platforms enable a better communication and connection with the teams. Facebook and Instagram are the most used social media platforms. Conclusion: From this current research we can conclude that social media marketing by using social media platforms (mostly Facebook and Instagram) can attract people toward more engagement with their sports team. One cause is that Facebook as well as Instagram are almost effortless to have access to and also very frequently utilized nowadays. Furthermore, social media platforms are easier to convey the ideas visibly eliminating the misunderstandings also the major cause is that it saves the time of people as well as it may efficiently convey the message than any other social media platforms. All of these showings can help sport managers to better understand the wants of the fans and there increase engagement through these platforms.